PWE-134 The Effectiveness and Patient Satisfaction of Specialist Screening Practitioner (SSP) Pre-Contact Telephone Clinic in Bowel Scope Screening. (17th August 2016) - Fitzgerald, G; Mbuyongha, M; Sarkar, S; Gaglia, A; Mumtaz-Wong, S
Abstract : Introduction: Bowel Scope is preventive intervention for colorectal cancer with a one off flexible sigmoidoscopy in the population at age 55 years. However, the invasive 'intrusive & unpleasant' nature, the requirement of patients to self-administer their enema and that only written information is supplied as standard prior to the procedure are all likely to impact on population uptake. Aims: On setting up Bowelscope at the Liverpool and Wirral Bowel Screening Centre, we trailed and then adopted a Pre-Contact SSP Telephone Clinic (PCTC) prior to Bowel scope with the aim to reassure and verbally inform patients and offer an opportunity for any questions and answers. This study was to evaluate the effectiveness of the Pre-Contact Clinic by reviewing the positive and negative impact of the clinic by reviewing the effect on patient satisfaction. Methods: This study was performed from 4/15 to 12/15 at the Liverpool & Wirral Bowel Screening Service and included 692 patients. Trail Phase : During the initial 4 month phase of roll out 1 Bowel scope list per week was performed. We trialled the PCTC by targeting alternate lists during this phase. Adopted Phase: following initial analysis, for the next phase- all confirmed patients were booked into a PCTC. Patient Satisfaction was measured in all patients and DNA rates monitored. Results: Trial Phase : In the trial phase 45.7% patient were booked into PCTC with 87.9% successfully contacted. In the standard listed patients the DNA rate was 7.2%. This compared to just 3.9% in the PCTC lists. Additionally, the patient satisfaction scores for these lists were extremely high compared to the standard lists. Adopted Phase: 77% capture of patients for PCTC. The DNA rate in those contacted was just 1.1% compared to 6.4% in those where pre-contact was NOT possible. In terms of patient satisfaction 98.8% of patients found PCTC useful. When rating the usefulness, the median score was 9 and mode score was 10 (scale where 1 was not at all useful & 10 was extremely useful). The themed items cited were reassurance (55%), opportunity to get advice and ask questions (34%) and others (17%). An additional advantage was that although 22 patients had already chosen to not proceed but had not informed the centre or hub, due to being contacted we have had the opportunity to utilise the slots instead of them being lost to DNA. Conclusion: SSP Pre-contact Telephone Clinic (PCTC) has made a significant impact on our Bowelscope service for us and particularly for the patients. As a consequence our DNA is very low and almost exclusively in the non-contacted patients. Patients are extremely satisfied with this model and it has had an impact on the uptake of Bowel scope in our centre. Disclosure of Interest: None Declared